Pengembangan E-LKPD Berbasis Google Sites Bercirikan Pendekatan Saintifik untuk Membangun Pemahaman Konsep Matriks - Wisnu Dharma Basudewa; Diesty Hayuhantika (ARITHMETIC: Academic Journal of Math, 2022)
One way to build understanding of the concept is to make innovations about E-LKPD. This study is aims to develop on process, the process result an E-LKPD based google sites on matrix material using a scientific approach to build a valid understanding of students' concepts. This study refers to one development model, namely the Four-D  (4-D) is Define, Design, Development, and Disseminate. In this study, the researcher modified the Four-D with 3 stages, namely Define, Design, and Development. The results showed that the feasibility level of the E-LKPD based  google sites on the matrix material based on the research of media experts all aspects got a total score of 101, so that when presented the validity of the media it got a value of  78.9% with the "Eligible" category. Furthermore, the feasibility of the E-LKPD based on google sites based on material experts got a total score of 209, so that when presented, media validity got one of the values of 84.2% with "Very Eligible" this category. The response from practitioners, namely the mathematics teacher, got an overall score of 146, so that if presented, it got a score of 86.90% in the "Very Eligible" category. The last trial on students of class X MIPA 2 a total of 9 people with a small group trial got a score of 325, so when presented it got a value of 90.27% with the "Very Eligible" category. This is the E-LKPD based on google sites using a scientific approach to class XI matrix material.